Multiscale surface texture and fractal analysis of straight bevel gears finished by PECH and PECF process - Talu, Stefan; Kulesza, Slawomir; Bramowicz, Miroslaw; Pathak, Sunil; Jain, N. K. (Taylor & Francis, 2019)
The present work was conducted to provide insights for an in-depth understanding of the straight bevel gears finished by pulsed-electrochemical-honing (PECH) and pulsed-electrochemical-finishing (PECF), using multi-scale surface texture and fractal analysis in order to give manufacturers a competitive edge when improving their tools. Unfinished bevel gears and bevel gears finished by PECF and PECH were analyzed on their surface texture characteristics and material properties. Surface characteristics of 20MnCr5 alloy steel gears were evaluated by computing four locations on regions of each sample. Field emission scanning electron microscopy (FESEM) was applied for surface material characterization. It was found that it can be discriminated between the PECF and PECH-finished bevel gears surface regions of samples and unfinished samples, using area-scale analysis and surface texture characteristics. The surface micro-morphology results can be applied in studies about improving the lifetime of tools and for mathematical modeling of lubrication processes between tool and workpiece.